Anaerobic ammonium oxidation-denitrification synergistic interaction of mature landfill leachate in aged refuse bioreactor: Variations and effects of microbial community structures. (November 2017) - Wei, Huawei; Wang, Jie; Hassan, Muhammad; Han, Lu; Xie, Bing
Graphical abstract: Highlights: Anammox-denitrification process occurred in aged refuse bioreactor (ARB). ARB could efficiently remove TN, NH4 + -N and NO2 − -N of leachate. The increase of HLR from 15 to 35 L/m 3 ·d could not inhibit the anammox efficiency. Changes in amx gene under different conditions were significant. Microbial community was richer at lower HLR and higher BOD5 /TN ratio, respectively. Abstract: In this work, anammox-denitrification process was verified by 15 N stable isotopic tracing methods and variations and effects of microbial community structures were studied using Illumina MiSeq sequencing and Quantitative Polymerase Chain Reaction (qPCR). The results showed that higher nitrogen removal efficiency and richer microbial consortia was observed at hydraulic loading rate (HLR) of 15 L/m 3 ·d, BOD5 /TN ratio of 0.4:1, respectively. Proteobacteria, Chloroflexi, Acidobacteria and Firmicutes were the dominant phyla in the anamox-denitrification biomass. The number of amx gene changed significantly during the HLR downshift and BOD5 /TN ratio upshift period. The obtained results enhance understanding regarding the microbial community structures of anammox-denitrification bacteria in aged refuse, leading to a more effective controlling of anammox-denitrification process.